Structural, optical and electrical properties of Cu2Zn1−xCdxSnS4 quinternary alloys nanostructures deposited on porous silicon - Ibraheam, A.S.; Al-Douri, Yarub; Al-Fhdawi, J.M.S.; Al-Jumaili, H.S.; Verma, K.D.; Hashim, U.; Ayub, R.M.; Rahim Ruslinda, A.; Md Arshad, M.K.; Reshak, A.H.; Hamid, Sharifah Bee Abd (Springer Verlag (Germany), 2016)
The Cu2Zn1−xCdxSnS4 quinternary alloy nanostructures with different Cd contents were grown using spin coating technique on porous silicon (63.93 %) substrate. The structural properties of Cu2Zn1−xCdxSnS4/PS were investigated by X-ray diffraction and field emission-scanning electron microscope (FE-SEM). The optical properties studied through photoluminescence technique, indicated that the band gap is shifted as Cd content increases from 1.84 eV at x = 0 to 1.76 eV at x = 1. The electrical characterization of the Ag/n-PS/Cu2Zn1−xCdxSnS4/Ag diode through current to voltage (I–V) characterization shows the highest photo-response of (value if any) at Cu2Zn0.4Cd0.6SnS4 composition.